Adropin as an indicator of T2DM and its complications - Hu Zhang; Ning Chen (Food Science and Human Wellness)
Type 2 diabetes mellitus (T2DM) is one of metabolic diseases with the major inducer of obesity. Due to the change in lifestyle and dietary structure, more and more people are being suffered from T2DM. Therefore, the prevention and treatment of T2DM and its complications has become an urgent problem to be solved. As a secreted peptide, adropin is identified as a useful regulator associated with insulin sensitivity and energy homeostasis. It has the potential for regulating metabolic diseases including obesity and T2DM. It should be noted that the secretion of adropin can be induced by diets, aerobic exercise and other interventions. In this article, the underlying mechanisms of adropin for regulating obesity, T2DM and its complications including diabetic nephropathy, diabetic retinopathy, diabetic encephalopathy, diabetic vascular disease and diabetic cardiovascular disease were summarized. Meanwhile, the strategies for promoting the secretion of adropin were also discussed, which will provide a target for the prevention and targeted treatment, or a candidate of novel and effective functional food or drug for metabolic diseases in the future.